Loads and hull-pressure measurements on a generic submarine in different stages of model build-up. (1st March 2023) - Lee, S.-K.; Jones, M.B.; Quick, H.
Abstract: This is an experimental study of loads and surface pressure on a generic BB2 submarine in different stages of model build-up. The build-up is from a bare hull to a fully-appended hull consisting of a casing, 4 aft control surfaces in an X-form configuration, a vertical sail fin and 2 horizontal sailplanes. The test is carried out in the Defence Science and Technology Group low-speed wind tunnel on a 2 m long hull at a freestream velocity of 60 m/s, where the hull-length Reynolds number is 8 million. The load trends are established for incidence angles up to 12 ∘, where the measured forces are up to 89 N for pure pitch and 163 N for pure yaw. The drag force is up to 14 N. Overall, the load trends are well approximated by high-order polynomials. From constructed pressure-gradient maps of the hull, the effect of model build-up can be observed in the changing pressure footprint and interpreted by using flow topology. Highlights: A BB2 submarine is tested in 5 stages of model build-up at a high Reynolds number Load trends are established for pure pitch and for pure yaw up to 12 degrees Pressure maps are constructed to allow interpretation of the separating flow